INFLUENCE OF PUBLIC POLICY, PARTICIPATION OF COMMUNITY AND EDUCATION LEVEL TO PUBLIC WELFARE IN PADANG PARIAMAN DISTRICT - Rizki Afri Mulia (Jurnal EL-RIYASAH, 2019)
Development must cover all areas as a whole. Partial development will be difficult to solve problems that arise can even exacerbate existing problems and create new problems. Development that focuses only on one aspect will lead to development failure. This research aims to know: 1) Influence of public policy toward society prosperity in Regency of Padang Pariaman, 2) Influence of Public Participation to society prosperity in Regency of Padang Pariaman, 3) Influence of education level to society prosperity in Padang Pariaman Regency.The data were collected by survey method with questionnaire. Data analysis technique used in this research is descriptive and quantitative analysis. The data collected are primary and secondary data that can be classified as independent variable and dependent variable. Public policy, public participation, and educational level (independent variables), and the welfare of society in Padang Pariaman (variable affected). Hypothesis testing in this study using multiple linear regression test.Based on the results of the research note that: 1) Public policy significantly influence the prosperity of the people of Padang Pariaman Regency. This means that the better public policy the better the welfare of the community that is produced 2) The community participation significantly influence the welfare of the people of Padang Pariaman Regency. That is, the increasing number of community participation in the implementation and supervision of the resulting community welfare will be better also 3) The level of education significantly affects the welfare of the people of Padang Pariaman Regency. That is, the higher education in a region or community will be the higher the welfare of the community in the area.